Unsuccessful Intervention of CT-Assisted Osteosynthesis for Stress Fractures of the Hook of the Hamate: A Report of 3 Cases. Issue 2 (April 2021) - Satake, Hiroshi; Naganuma, Yasushi; Shibuya, Junichiro; Honma, Ryusuke; Nito, Toshiya; Takagi, Michiaki
Abstract : Case: We performed computed tomography (CT)-assisted dorsal approach osteosynthesis for stress fractures of the hook of the hamate using the dorsal approach in 3 high school baseball players in the hybrid operating room. Bony union was observed in all patients on CT. All patients were able to play baseball without pain for at least 6 months after surgery. However, refractures were observed in all patients at a mean 9.7 months after surgery. Conclusion: The indications of osteosynthesis for stress fractures of the hook of the hamate in baseball players should be carefully considered.